Pesca de linha no litoral cearense: risco ecológico e sustentabilidade dos teleósteos - Marques, Jasna Maria Luna (2022)
Artisanal fisheries are a source of livelihood for small-scale fishers around the world. One of the most used gears in these fisheries, which in tropical regions are usually multi- species, is the handline. The risk of overfishing is a constant concern for traditional fishing communities. Therefore, studies are needed to support the management of these fisheries by providing data that will lead to sustainable catches. The data for this study, which was divided into three chapters, were collected by monitoring the fishing landings. The collections occurredtwice a month in the periods from May 2017 to April 2018, at Mucuripe beach, from July 2018to June 2019 in the Batoque resex and from April 2017 to April 2018 in the Prainha do Canto Verde resex. Specimens were identified, counted, measured and weighed. Ecological and biological data of the species published in scientific articles and on the FISHBASE platform and conservation data in the International Union for Conservation of Nature (IUCN) were also used. In all, 254 vessels were sampled and 85 species were identified on the three beaches. In Chapter 1, the dynamics of the handline fishery at sites with different management regimes was studied, characterizing the effort, abundance, and CPUE of the fisheries. The highest landings were recorded at Mucuripe (10.16 ton), which also had the highest median production (122 kg), effort (762 hook*h) and the highest number of species caught differed among locations. There was no difference in fishery productivity between the locations with different management types studied. In chapter 2, with the help of productivity and susceptibility analysis (PSA), the sustainability of the catch of the most fished species at these sites with different management regimes was evaluated. Productivity values ranged from 1.24 to 2.88. The species Scomberomorus cavalla and Holocentrus adscensionis obtained the highest and lowest risk scores, respectively. Susceptibility values ranged from 1.18 to 2.27. The species Lutjanus synagris at Batoque received the highest susceptibility score, due to the high value in the commercial category, frequency of occurrence and abundance. Vulnerability values were between 1.71 and 3.46. The species S. cavalla, L. analis and Ablennes hians were the most vulnerable, ranked as high risk at all locations. The species H. adscensionis was the least vulnerable at all locations. However, the vulnerabilities did not differ statistically between locations. In chapter 3, through modeling in Ecopath software, a trophic structure model of Mucuripe beach with the intervention of artisanal fisheries was developed, using ecosystem indicators. The model was established with 32 compartments, where the ones with the highest trophic level (NT) were sharks (3.54) and dolphins (3.46) and the mean NT was 2.54. The mean value of the Pedigree index was satisfactory (0.50365). The fishery focuses more on NT III. The value of the L index was 0.0026 (± 0.0005), indicating that the Psust is greater than 95% 11 and its value was approximately "1", revealing that the fishery is sustainable. The highest ecosystem biomasses were of the "detritus" and "invertebrates" compartments, while the fish, were "Haemulon spp" and "Lutjanus jocu". The Lindeman diagram showed the relevance of the primary producers and detritus to the trophic web. The flows from these compartments amount to 40.31% and 37.27% of the total flows. The most important compartments for the maintenance of the trophic structure of Mucuripe are "other piscivores", "dolphins", "phytoplankton" and the species "H. adscensionis" and Cephalopholis fulva". The artisanal fishing activity is of social and economic importance, and it is necessary to monitor the status of the exploited populations for its full management.